Respiratory Impairment and Personal Respirable Dust Exposure among the Underground and Open Cast Gold Miners in Tanzania - Matilda Rusibamayila (Ubiquity Press, 2018)
Background: Mining is one of the most hazardous sectors to work in because it predisposes workers to various hazards including dust. Exposure to dust is inevitable in the mines because the process of extracting gold involves breaking rocks. This dust can penetrate up to the alveoli of the pulmonary system and cause respiratory impairment. Objectives: To determine respiratory impairment, personal respirable dust exposure levels and associated factors among miners in a gold mine in Tanzania. Methods: Cross-sectional study design, employing questionnaire, was used for data collection on respiratory symptoms. Lung functions were measured using spirometry. Personal respirable dust exposure was collected from similar exposure groups using air sampling pumps. A simple random sampling technique was used to select 112 participants of the study. Data analysis was done using SPSS computer software version 20.0. Results: The overall geometric mean (GM) of respirable dust was 0.26 mg/m3 (GSD = 0.32) over a mean sampling time of 8 hours (with a range between 7–11 hours). The GM of respirable dust for underground workers was significantly higher (0.41 ± 0.28 mg/m3) compared to the open pit workers (0.17 ± 0.23 mg/m3) with p < 0.01. For underground workers, the GM of respirable dust was the highest among the bogger operators at 0.53 mg/m3 (GSD = 0.27). For open pit workers, the highest GM of respirable dust was found among the quality controllers at 0.39 mg/m3 (GSD = 0.18). Respiratory symptoms were phlegm (49.1%), breathlessness (42.9%), cough (37.5%), wheezing (18.8%) and chest tightness (10.7%). Cigarette smokers were more likely to suffer from breathlessness than nonsmokers. The prevalence of airflow obstruction (FEV1/FVC < 0.7) was 1.9%; whereas, the prevalence of lung restriction was 8.8%. The study established that age, smoking habit and previous exposure to dust could not predict lung function impairment. Conclusion: Despite levels of respirable dust exposure being below the recommended occupational exposure limits, the prevalence of respiratory symptoms was still found to be high among the studied gold miners. This calls for a need to conduct further studies on quartz content of the respirable dust.